2016
DOI: 10.1177/0004867416671415
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic brain abnormalities in young healthy adults with childhood trauma: A resting-state functional magnetic resonance imaging study of regional homogeneity and functional connectivity

Abstract: The present outcomes suggest that childhood trauma is associated with disturbed intrinsic brain function, especially the default mode network, in adults even without psychiatric diagnoses, which may mediate the relationship between childhood trauma and psychiatric disorders in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 50 publications
(57 reference statements)
3
27
0
Order By: Relevance
“…A prominent finding is reduction of FC in the default mode network (DMN) [ 9 , 10 ], while other key findings include disruptions in emotional processing networks [ 11 ], executive network [ 12 ], salience network [ 13 ], and amygdala-DMN, as well as insula-hippocampus connectivity [ 14 ]. In accordance with these findings, our prior study also reported that childhood trauma, in the absence of psychiatric diagnosis, was associated with altered DMN, cerebellum-DMN, and insula-DMN connectivity, along with regional homogeneity (ReHo) changes in the inferior parietal lobule (IPL), superior temporal gyrus (STG), insula, cerebellum, and middle temporal gyrus [ 15 ]. Meanwhile, Philip et al (2013) used ReHo approach based on whole brain analysis and found a correlation of brain regional dysfunction in the IPL and STG with early life stress as well [ 16 ], suggesting that childhood trauma not only impacts FC but also brain regional activity.…”
Section: Introductionsupporting
confidence: 62%
“…A prominent finding is reduction of FC in the default mode network (DMN) [ 9 , 10 ], while other key findings include disruptions in emotional processing networks [ 11 ], executive network [ 12 ], salience network [ 13 ], and amygdala-DMN, as well as insula-hippocampus connectivity [ 14 ]. In accordance with these findings, our prior study also reported that childhood trauma, in the absence of psychiatric diagnosis, was associated with altered DMN, cerebellum-DMN, and insula-DMN connectivity, along with regional homogeneity (ReHo) changes in the inferior parietal lobule (IPL), superior temporal gyrus (STG), insula, cerebellum, and middle temporal gyrus [ 15 ]. Meanwhile, Philip et al (2013) used ReHo approach based on whole brain analysis and found a correlation of brain regional dysfunction in the IPL and STG with early life stress as well [ 16 ], suggesting that childhood trauma not only impacts FC but also brain regional activity.…”
Section: Introductionsupporting
confidence: 62%
“…The present study also found that CA was positively associated with connectivity of the PCC to bilateral sensory-motor regions and a mid-dorsal cingulate region. This is similar to previous reports of altered connectivity in the DMN in healthy young adults (Lu et al ., 2017 ). Associations between CA and blood-oxygen-level dependent (BOLD) responses to the anticipation of aversive stimuli in the motor cortex and left insula were reported by another group (Duncan et al ., 2015 ); thus, one possibility is that the sensory-motor findings in the present study may represent an increase in intrinsic connectivity between the DMN and aversion-related networks in individuals with higher CA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is difficult to infer whether alterations following early adversity are evident only in subjects who later develop psychiatric disorders, or whether these changes are detectable consequences of maltreatment in subjects with no psychiatric disorder history and accordingly constitute promising vulnerability markers. One study included healthy controls without current or lifetime psychiatric disorders which investigate the regional homogeneity and function connectivity under resting-state fMRI (Lu et al, 2017). To overcome these limitations, we applied the Montreal Imaging Stress Task (MIST), which comprises a series of computerized mental arithmetic tasks with an induced failure component and was developed to fit the constraints of the imaging environment (Dedovic et al, 2005), to investigate effects on physiological stressors and brain activation in healthy young subjects without psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%